In the opinion of scientists: are there rules in research? Pilot study on the most widespread rules of scientific research - de la Lama-Zubirán, Paula (2021)
Sociologists, ethnologists, philosophers among others have tried to identify the norms or rules that govern scientific research; however, so far, they have not been widely accepted by scientists. This team followed a different path to identify the rules that govern scientific work by asking researchers if, in their opinion, there are rules in scientific research, and, if so, what they are. An opinion poll was conducted among 270 scientists who received academic training at universities in Mexico, Europe, and the United States, and who work at three universities in Mexico. The instrument is based on a social psychology theory that divides memories into spontaneous and assisted, and a dichotomous probability distribution was used to identify variations. Between eight and nine out of ten researchers from physical, biological, and social sciences recognized that there are four rules for research: to study reality as it is, have a critical attitude, have a methodological aptitude, and express willingness to openly publish results. Despite the heterogeneity of the disciplines researchers practice and the variety of their academic training, there is a consensus among scientists about the validity of such rules to conduct scientific research, although most of the time they do not mention them spontaneously.